La actividad petrolera y el empleo en el departamento de Loreto periodo 2019-2023 - Del Aguila García, Luis Alberto (2025)
Over the years, the department of Loreto had oil activity as the main activity in its economy, and also the largest demander of direct and indirect labor. The purpose of this doctoral thesis is to determine if the oil activity is related to the employment of Loreto in the five-year period 2019 – 2023. The applied methodology has to do with the analysis of historical series, making it typified as a Quantitative according to its nature. , and with evidencing the existence of an association between variables, making it Correlational. The research design is Non-Experimental. It is concluded that there is no statistical association between oil production and employment in Loreto, in the period 2019 - 2023, since the Correlation Coefficient was r = -0.295289938; and the Coefficient of Determination was R2 = 0.087196148. Extraction of Oil, Gas and Minerals was the economic activity that contributed the most to the Gross Added Value of Loreto (18.46%), followed by Commerce activity with a contribution of 16.92%. The lot located in Loreto with the highest production of crude oil was Lot 95, the same one that produced 16,362.00 thousand barrels during the five-year period, equivalent to 70.66% of the total. Finally, the branch of economic activity that concentrated the largest number of workers was Agriculture and Fishing, employing 788,948.00 people during the five years of study, equivalent to 30.71% of the total.